Alone in silence European women in the Canadian North before 1940 - Kelcey, Barbara E. (Barbara Eileen), 1949-; ebrary, Inc. (Montréal : McGill-Queen's University Press, 2001)
This book details the struggles of the over 500 European women who travelled or lived in Canada's Northwest Territories before 1940 to set up a home in the harsh environment. The geography also forced them to adjust they way they worked. For instance, letters and reports of the Grey Nuns who worked alongside the Oblate Fathers in the Mackenzie indicate the hardships imposed by their situation but also show how driven they were by their missionary purpose.
Includes bibliographical references (p. [207]-219) and index.
Electronic reproduction.
Keywords: Women, White -- Canada, Northern -- History; Europeans -- Canada, Northern -- History; Frontier and pioneer life -- Northwest Territories; Canada, Northern -- Social conditions; Northwest Territories -- History; Electronic books